Adjustment factors of birth weight and four postnatal weights for type of birth and rearing, sex of lambs and dam age - ., Subandryo; Vogt, D.W (Indonesian Journal of Animal and Veterinary Sciences, 1995)
Many factors contribute to variation in lamb weights . Factors such as age of lamb, sex, type of birth and rearing, and ewe age at lambing obscure genetic differences among lambs . Variation associated with these factors make selection for increased weight less effective . To improve selection response, selection must be based on genotypic rather than environmentally induced superiority . It is well-documented that corrections for classifiable sources of variation render selection and culling more accurate, thereby increasing rates of genetic improvement . The objective of this study were to develop within breed adjustment factors for post-natal lamb weights . Field records from Suffolk and Dorset lambs collected in the U.S . National Sheep Improvement Program (NSIP) from 1986 through 1989 were used to develop within-breed birth/rearing type, lamb sex, and dam age adjustment factors for birth weight (BW) and 30-d (W3o), 60-d (Woo), 90-d (W9o), and 120-4 (Wtm) weights. Data were analyzed using general linear models . Within breed and age group adjustment for lamb-age differences were suggested because growth rates vary among breeds and among the four postnatal lamb-age groups . Within-breed multiplicative adjustment of the five traits for the effects of birth/rearing type, lamb sex and dam age were suggested because variances of these factors were significantly (P<0.01) heterogenous Â  Key words: Sheep, adjustment factors, birth weight, postnatal weights